Antimicrobial multiple resistance index, minimum inhibitory concentrations, and extended-spectrum beta-lactamase producers of Proteus mirabilis and Proteus vulgaris strains isolated from domestic animals with various clinical manifestations of infection - Zappa, Vanessa; Bolaños, Carmen Alicia Daza [UNESP]; De Paula, Carolina Lechinski [UNESP]; Callefe, João Luis Revolta [UNESP]; Alves, Ana Carolina [UNESP]; De Morais, Amanda Bonalume Cordeiro [UNESP]; Guerra, Simony Trevizan [UNESP]; Cabrini, Marina Chaves; Melville, Priscilla Anne; Ribeiro, Márcio Garcia [UNESP] (Universidade Estadual de Londrina, 2017)
Proteus spp. are opportunistic multidrug resistant enterobacteria associated with diverse clinical diseases in domestic animals. However, Proteus infections in domestic animals are often misdiagnosed or considered contaminants in microbiological cultures rather than a primary agent of disease. Descriptions of Proteus infections in domestic animals are typically restricted to case reports, retrospective studies, or surveillance of other microorganisms. The present study investigated multiple antibiotic resistance indices, minimum inhibitory concentrations (MICs), and ESBL production in 73 strains of Proteus mirabilis (n = 69) and Proteus vulgaris (n = 4) isolated from domestic animals with various clinical manifestations. In dogs, the pathogen was most commonly associated with cystitis (48.21), enteritis (21.42%), otitis (14.29%), and conjunctivitis (3.57%). In bovines, the microorganism was predominant in cases of enteritis (22.22%), abscess (11.11%), otitis (11.11%), omphalitis (11.11%), and peritonitis (11.11%), and in organ fragments (11.11%). In equines (50.0%) and cats (100.0%), diarrhea was the main clinical sign. In vitro standard disk diffusion assay showed that the most effective antimicrobials against the isolates were imipenem (98.63), norfloxacin (95.89), amikacin (95.89), levofloxacin (90.41), ceftriaxone (87.64), and florfenicol (87.67). In contrast, the isolates commonly showed resistance to novobiocin (95.89), azithromycin (57.53), and trimethropim/sulfamethoxazole (39.73). Among the 73 isolates, the efficacy of amoxicillin/clavulanic acid, gentamicin, ceftriaxone, and ciprofloxacin according to MICs was 87.67%, 86.30%, 84.93%, and 82.19%, respectively. The MIC50 values of amoxicillin/clavulanic acid, ceftriaxone, ciprofloxacin, and gentamicin were, respectively, 1.0, 0.004, 0.03, and 1.0 μg/mL. Thirty-three strains (45.21%) showed a antimicrobial multiple resistance index of ≥0.3. Multidrug resistance profiles of isolates were observed most frequently in dogs (n = 25; 75.76%), particularly in those with cystitis (n = 13; 52.0%), followed by bovines (n = 4; 12.12%), equines (n = 2; 6.06%), and cats (n = 2; 6.06%). Two (2.7%) strains, obtained from canine skin and feces, were diagnosed phenotypically as ESBL-producers. Here, we observed the diversity of Proteus infections in domestic animals. The presence of multidrug-resistant isolates and ESBL-producers reinforces the need for appropriate antimicrobial use and in vitro antimicrobial tests to support therapy.
Keywords: Companion animals; Extended-spectrum beta-lactamase; Livestock; Multidrug resistant; Proteus sp